2010
DOI: 10.1098/rsif.2010.0118.focus
|View full text |Cite
|
Sign up to set email alerts
|

Titanium oral implants: surface characteristics, interface biology and clinical outcome

Abstract: Bone-anchored titanium implants have revolutionized oral healthcare. Surface properties of oral titanium implants play decisive roles for molecular interactions, cellular response and bone regeneration. Nevertheless, the role of specific surface properties, such as chemical and phase composition and nanoscale features, for the biological in vivo performance remains to be established. Partly, this is due to limited transfer of state-of-the-art preparation techniques to complex three-dimensional geometries, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
194
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 82 publications
0
194
0
7
Order By: Relevance
“…By sputtering in a reactive environment (O 2 ), the intention was to enhance both bioactive and antibacterial properties of the coating, as formation of TiO 2 facilitates osseointegration by providing chemical stability and increased wettability [16,19,20,43], and incorporation of oxygen in silver is known to affect its dissolution rate [44]. The concurrent, reactive sputtering in this instance made for a compositional Ag-Ti oxide gradient with a dominant crystalline contribution from Ag.…”
Section: Discussionmentioning
confidence: 99%
“…By sputtering in a reactive environment (O 2 ), the intention was to enhance both bioactive and antibacterial properties of the coating, as formation of TiO 2 facilitates osseointegration by providing chemical stability and increased wettability [16,19,20,43], and incorporation of oxygen in silver is known to affect its dissolution rate [44]. The concurrent, reactive sputtering in this instance made for a compositional Ag-Ti oxide gradient with a dominant crystalline contribution from Ag.…”
Section: Discussionmentioning
confidence: 99%
“…The laser irradiation on the titanium surface may promote the osteoblast attachment and further bone formation. Palmquist et al 53 made an in-vivo study of laser modified titanium and nano-scale surface topographic features. The authors concluded that the torque removal significantly increased in the lasermodified implant and of clinical importance, the nanostructured surfaces supported long-term bone bonding and interface strength between the titanium implant and the bone.…”
Section: Laser Modificationmentioning
confidence: 99%
“…Different specialties within the dental profession take advantage of this material. Titanium alloyed with elements such as nickel, molybdenum or copper has widespread use in orthodontics [3]; the combinations of this metal with others, such as aluminium or vanadium, are used in oral rehabilitation, implantology [1,4,5], and maxillofacial surgery [6][7][8].…”
Section: Introductionmentioning
confidence: 99%